The Effect Of The Combination Of Cinnamon Powder Infusion And Honey On Reducing Blood Sugar Levels In Type II Diabetes Mellitus Patients In RT 007 And 008 / RW 05, Balekambang Subdistrict, East Jakarta - Utomo, Muhamad Tridhal Dadi; Susanti, Dewi; Dinaryanti, Ratna Sari (Jurnal EduHealth, 2024)
Diabetes Mellitus is a metabolic disorder caused by impaired insulin function, leading to hyperglycemia (blood sugar <200 mg/dL). Its management includes pharmacological therapy (insulin) and non-pharmacological approaches, such as the use of cinnamon powder and honey. This study aims to determine the effect of the combination of cinnamon powder and honey on reducing blood sugar levels in Type II Diabetes Mellitus patients in RT 007 and 008/RW 05, Balekambang Subdistrict, East Jakarta. The research design used was a quasi-experimental design with a one-group pre-test post-test without control. The population consisted of Type II Diabetes Mellitus patients, with a sample of 32 respondents selected through consecutive sampling. The research instruments included a glucometer, observation sheets, cinnamon powder, and honey. Statistical analysis was performed using the Paired T-test. The results showed the average blood sugar level before the intervention (247.0 mg/dL) and after the intervention (222.7 mg/dL) using the combination of cinnamon powder and honey. The test results indicated a significant relationship between the combination of cinnamon powder infusion and honey with a reduction in blood sugar levels in Type II Diabetes Mellitus patients in RT 007 and 008/RW 05, Balekambang Subdistrict, East Jakarta, with a p-value = 0.000 < 0.05. This study provides recommendations for nursing services to implement non-pharmacological therapy to reduce blood sugar levels.